A Flow Stress Model of the AA3104-H19 Alloy for the FEM Simulation of the Beverage Can Manufacturing Process under Large Plastic Deformations - Przemysław Wędrychowicz (MDPI AG, 2021)
This paper discusses the development of a flow stress model to simulate the AA3104-H19 alloy under the conditions of large plastic deformations characteristic of the beverage can manufacturing process. This study focuses on the first five steps of this process: cupping, redrawing, ironing #1, ironing #2, ironing #3. These are the stages that reduce the thickness of the base material to the maximum, resulting in an effective strain of more than 2.0, unattainable in conventional plastometric tests. To solve this problem, the specific calculation-experimental method for the development of the flow stress model was proposed. Based on the FEM modeling of the technological process, data on the history of deformation and the trajectory of movement of the selected points of the material at all stages of the production were obtained. Microspecimens for the tensile tests were taken from the points of the beverage can wall that were determined in this way. The initial strain of each sample was taken from the FEM simulation. In this way, the tensile curves were obtained for the material points at different stages of the production. The processing of these curves allowed the creation of a flow stress model for large strains, corresponding to production conditions. The tensile tests were performed on a Zwick Z250 machine at room temperature and strain rate of 0.005 s−1. The FEM-based algorithm for the determination of empirical coefficients of the analytical flow stress model is presented. The final flow stress model covers the range of effective strain from 0–2. Validation of the developed model based on the measured beverage can thicknesses showed that a flow stress model was developed that correctly and accurately describes the forming process.